Prevalence of gastrointestinal parasites and anthelmintic efficacy in sheep and goats under different management and deworming systems in the region of Lisbon and Tagus Valley, Portugal - Antunes, Maria Inês Caetano (2022)
Dissertação de Mestrado Integrado em Medicina Veterinária